Beyond Partnerships: The Power Of Lean Supply Chains (2007)
Extending the value stream from a lean company to its partners allows the company to widen the pursuit for perfection to the whole supply network. Furthermore, applying lean concepts to a supply chain opens new windows of opportunity for supply chain participants to collectively achieve higher levels of competitiveness. Thus, the integration of supply chain management and lean thinking covers both local and overall leanness, which leads to a truly lean supply chain. This chapter provides an overview of the lean supply chain, the including concepts, approaches, challenges, and future development. In the first part of the chapter, basic concepts and impacts of lean thinking will be introduced, followed by the issues of applying lean thinking in supply chain management. Then, an integrated framework of a lean supply chain will be presented. The second part of the chapter covers the building blocks of lean supply chains, including lean logistics, information technology, performance measurement and improvement, and collaboration beyond partnerships. Subsequently, the challenges for building or maintaining a sustainable lean supply chain will be discussed.